Horizontal gene transfer contributes to plant evolution: The case of agrobacterium T-DNAs - Quispe-Huamanquispe D.G. (2017)
The authors gratefully acknowledge the financial support provided to DQ-H from the Special Research Fund (BOF) of Ghent University, Belgium (01W02112) and Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica (CONCYTEC) of the government of Peru. We acknowledge Robert L. Jarret and León Otten for critical review of the manuscript. Research by JK was undertaken as part of, and funded by, the CGIAR Research Program on Roots, Tubers and Bananas (RTB) and supported by CGIAR Fund Donors (http://www.cgiar.org/about-us/our-funders/).